STUDY OF ETHNOMEDICINE TO REDUCE HEAT USING SEA FLOWER LEAF EXTRACT IN PULAU PAYUNG VILLAGE AS A SCIENCE LEARNING RESOURCE - Fatmawati, Nur Indah; Syarif, Muhammad Ilham (JURNAL EDUSCIENCE, 2024)
Fever can be defined as a condition where body temperature is above normal due to an increase in the regulation of body temperature located in the hypothalamus, resulting in a disturbance in the production and release of heat known as hyperthermia, which is the initial symptom of illness. Traditional treatment using medicinal plants provides insight that not only pharmacological drugs can reduce fever, but medicinal plants also have the efficacy to reduce fever, one of which is the efficacy of hibiscus leaf. The aim of this research is to explore the use of hibiscus leaf extract as an antipyretic drug in Kampar Regency, evaluate its effectiveness based on local and scientific knowledge, and provide recommendations to support the development and preservation of the use of hibiscus leaf extract as a safe and effective antipyretic. This research was conducted in April 2024 in Pulau Payung Village, Kampar Regency, Riau Province. Data collection includes primary data collected through observation techniques and interviews, while secondary data were obtained through literature studies and documentation. The results of the study show that the community's knowledge regarding the use of hibiscus leaf extract as an antipyretic drug is sourced from experience passed down from one generation to the next. This knowledge can be used as a learning source with an ethnoscientific approach in the field of ethnomedicine through the reconstruction of local community knowledge into scientific knowledge.Keywords: Ethnomedicine, hibiscus leaf, antipyretic medicine.Abstrak Demam dapat didefinisikan sebagai suatu keadaan suhu tubuh diatas normal akibat adanya peningkatan pengaturan suhu tubuh yang berada di hipotalamus terjadi gangguan produksi dan pelepasan panas yang disebut dengan hipertermi yang merupakan awal dari gejala penyakit. Pengobatan tradisional menggunakan tanaman obat ini dapat memberikan pengetahuan bahwa bukan hanya obat farmakimia saja yang dapat menurunkan demam, melainkan tanaman obat juga berkhasiat menurunkan demam salah satunya khasiat daun bunga sepatu. Tujuan penelitian ini adalah untuk mengeksplorasi penggunaan ekstrak daun kembang sepatu sebagai obat penurun panas di Kabupaten Kampar, evaluasi efektivitasnya berdasarkan pengetahuan lokal, ilmiah, dan memberikan rekomendasi untuk mendukung pengembangan dan pelestarian penggunaan ekstrak daun kembang sepatu sebagai obat penurun panas yang aman dan efektif. Penelitian ini dilakukan pada bulan April 2024 di Desa Pulau Payung Kabupaten Kampar Provinsi Riau. Pengambilan data meliputi primer yang dikumpulkan melalui teknik observasi dan wawancara sedangkan data sekunder dengan studi literatur dan dokumentasi. Hasil penelitian menunjukkan bahwa pengetahuan masyarakat terkait penggunaan ekstrak daun kembang sepatu sebagai obat penurun panas bersumber dari pengalaman yang diwariskan secara turun-temurun dari satu generasi ke generasi berikutnya. Pengtahuan tersebut dapat dijadikan sebagai sumber belajar dengan pendekatan etnosains pada bidang etnomedisin melalui rekonstruksi pengetahuan lokal masyarakat ke dalam sains ilmiah.Kata Kunci: Etnomedisin, daun kembang sepatu, obat penurun panas